An Invariably Stable Cobweb Model - Carlson, J. A. (Review of Economic Studies, 1968)
Journal Article An Invariably Stable Cobweb Model Get access J. A. Carlson J. A. Carlson Purdue University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 3, July 1968, Pages 360–362, https://doi.org/10.2307/2296670 Published: 01 July 1968